Computational Insights Into the Electronic Structure and Magnetic Properties of Rhombohedral Type Half-Metal GdMnO3 With Multiple Dirac-Like Band Crossings - Chang, Yu; Moon, Sung-Ryong; Wang, Xin; Khenata, Rabah; Khachai, H.; Kuang, Minquan (Frontiers in Chemistry, 2020)
In spintronics, half-metallic materials (HMMs) with Dirac-like cones exhibit interesting physical properties such as massless Dirac fermions and full spin polarization. We combined first-principles calculations with the quasi-harmonic Debye model, and we proposed that the rhombohedral GdMnO3 is an HMM with multiple linear band crossings. The physical properties of GdMnO3 were studied thoroughly. Moreover, the changes of multiple linear band crossings and 100% spin polarization under spin-orbit coupling as well as the electron and hole doping were also investigated. It is noted that such spin-polarized HMMs with linear band crossings are still very rare in 2D and 3D materials.